Mononuclear Iron(II) Dicarbonyls Derived from NNS Ligands – Structural Models Related to a "Pre‐Acyl" Active Site of Mono‐Iron (Hmd) Hydrogenase. Issue 10 (27th February 2015) - Muthiah, Keren A. Thomas; Durgaprasad, Gummadi; Xie, Zhu‐Lin; Williams, Owen M.; Joseph, Christopher; Lynch, Vincent M.; Rose, Michael J.
Abstract: We report the syntheses and characterization of dicarbonyliron complexes derived from tridentate, ortho ‐substituted Schiff base pyridine/thioether ligands (R NNS). Metalation reactions ofR NNS (R = CH3, OCH3 ) at low temperature (–78 °C) with [Fe(CO)4 (Br)2 ] afforded the desired complexes [(R NNS)Fe(CO)2 Br]Br (2 ‐COBr, 3 ‐COBr ). Reactions under similar conditions with more sterically demanding ligands [R = quinoline (Q), ClPh] afforded complex salts of the form [(R NNS)Fe(CO)2 Br][Fe(CO)3 (Br)3 ] (4 ‐COFe and5 ‐COFe, respectively). Alternatively, the metalation of theR NNS ligands (for all R ≠ H) with [Fe(CO)4 (Br)2 ] in Et2 O at room temperature reliably affords the complex species of type [(R NNS)Fe(CO)2 Br][Fe(CO)3 (Br)3 ] (2 ‐COFe, 3 ‐COFe, 5 ‐COFe ). The metalation reactions ofR NNS at only moderately low temperatures (–20 to 0 °C) result in the loss of CO to form the corresponding trigonal‐bipyramidal iron(II) dibromide species of type [(R NNS)FeBr2 ] (2 ‐Br, 4 ‐Br, 5 ‐Br; μ eff ≈ 5.3 μB, S = 2). The IR spectrum of each dicarbonyl cation exhibits two ν(CO) stretches at$\tilde {ν}$ ≈ 2070 and 2030 cm –1 . Low‐temperature 1 H NMR spectroscopy measurements of2 ‐CO to5 ‐CO in CD3 CN (–35 to 5 °C) revealed sharp resonances in the diamagnetic region. Under dark conditions, each dicarbonyl species is relatively stable (<10 % loss of CO, 1–2 h). However, photolysis revealed varying extents of photostability (stability rank: R = OMe > Me ≈ Q > ClPh). An examination of the structural parameters reveals that higher photostabilities correlate with shorter Fe–C(O) bond lengths, which are induced by variation of the ortho substituent of the pyridine ring. DFT calculations along the putative photolysis pathway revealed that the bulky ligand substituent (in5 ‐CO) destabilizes the monocarbonyl intermediate, and this is a likely explanation for its more rapid rate of CO photodissociation. Relevance to a possible "apo‐active site" of mono‐iron hydrogenase (pre‐acyl formation) is discussed. Abstract : A series of iron(II) dicarbonyls are prepared from neutral Schiff base (NNS) ligands. These "phosphine‐free" complexes are extremely temperature‐ and light‐sensitive and somewhat like the active site of mono‐[Fe] hydrogenase. The Fe(CO)2 ‐bound methylpyridine unit in [(Me NNS)Fe(CO)2 Br] + may represent a "snapshot" of an intermediate during the biogenesis of the Fe–C(=O)acyl ‐containing active site.